Ventromedial prefrontal cortex mediates visual attention during facial emotion recognition - Wolf, Richard C. (Oxford University Press, 2014)
The ventromedial prefrontal cortex is known to play a crucial role in regulating human social and emotional behaviour, yet the precise mechanisms by which it subserves this broad function remain unclear. Whereas previous neuropsychological studies have largely focused on the role of the ventromedial prefrontal cortex in higher-order deliberative processes related to valuation and decision-making, here we test whether ventromedial prefrontal cortex may also be critical for more basic aspects of orienting attention to socially and emotionally meaningful stimuli. Using eye tracking during a test of facial emotion recognition in a sample of lesion patients, we show that bilateral ventromedial prefrontal cortex damage impairs visual attention to the eye regions of faces, particularly for fearful faces. This finding demonstrates a heretofore unrecognized function of the ventromedial prefrontal cortex—the basic attentional process of controlling eye movements to faces expressing emotion.